Spatial analysis of urban expansion in Baqaa Governorate using remote sensing techniques and geographic information systems during the period (2000 AD - 2022 AD) - Al-Shammari, Seham Sayer; Al-Shammari, Haifa Hammoud (Journal of Humanities & Social Sciences, 2024)
Urban growth refers to the overall development experienced by peoples and nations as a result of their development and progress. It is the organizer of social and service relations. The Kingdom of Saudi Arabia has developed throughout its modern history in the era of rapid growth. Old houses into an administrative and service city. The current study refers to the reality of the urban development that Baqa’a Governorate went through in the Hail region during the period from 2000 AD to 2022 AD using geographic information systems and remote sensing tools and using historical, descriptive and analytical scientific methods to achieve this goal. The research comes in several chapters, in which it talks about the causes of urban growth and its human and natural determinants, in addition to studying the change of land uses in the Baqa’a Governorate, and determining the growth trends in it during the study period using ArcGIS 10.8, analyzing it, and extracting the results. The research showed the development of Baqa’a Governorate from a group of a small urban agglomeration to an administrative metropolis for the region, with an increase rate of about 58% in the last ten years of the study. The trends of urban development were also identified in it in a way parallel to the highway towards Hail, and also in the areas that were taken care of from By the Ministry of Municipal, Rural Affairs and Housing in Eastern Baqa’a. It also determined the built-up area at each stage and identified the neighborhoods that appeared in each of them, thus forming a scientific database that contributes to helping decision-makers develop sound and effective organizational plans in order to achieve the goals of the vision for the year 2030 AD.